Khamitova K.K., Yegemova S.S., Bauyrzhan M. Determination of soil toxicty bioassay method under the inﬂuence of phenol: 1Al-Farabi Kazakh National University, Kazakhstan, Almaty 2Center of Physical Chemical Methods of Research and Analysis, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
Soil is the basis of agriculture and the main source of food, providing95-97% of food resources for the world’s population. Significant negativeimpacts on soil pollution has toxic chemical compounds, many of whichare preserved for a long time in the soil.Phenol is a second class of danger to be carcinogenic and mutagenic.We studied the effect of harmful substances on the growth of radish seedssprouting. Experiments made in the laboratory on artificially contaminatedof phenol soil samples. It was established pattern of influence of the concentration of phenol in the soil extract on the growth of plants.The main sources of phenols into the environment are motor vehicleemissions, the production of phenol-formaldehyde resins, adhesives, plastics and steel, coke plants, etc. Phenol is in air, soil and water for a longtime if a large amount thereof ejected at a time, or if a large number ofemission occurred in a long time. When a one-time release of phenol inthe air less than a day, its concentration is halved on average. When injected into the soil phenol output 2-5 daysOne reason for the lack of data on contamination of soil phenol isquite complicated and expensive sample preparation required for its quantification. This places significant limitations on the number of samples analyzed and reduces the effectiveness of monitoring. At the moment, thereare only a few data on the results of determination of phenols in soils.The paper studied the effect of phenol on the growth of radish seedssprouting. The experiments were performed in the laboratory on artificially contaminated with phenol soil samples. Calculation of the degreeof change in seed germination and seedling root length as compared tocontrol samples allowed to correlate the contaminated with some degreeof toxicity. It was established pattern of influence of the concentration ofphenol in the soil extracts on the growth of plants.Кey words: phenol, toxicity, soil, radish, express test.